2022
DOI: 10.1364/oe.467502
|View full text |Cite
|
Sign up to set email alerts
|

Fringe projection profilometry method with high efficiency, precision, and convenience: theoretical analysis and development

Abstract: Fringe projector profilometry (FPP) is an important three-dimensional (3D) measurement technique, especially when high precision and speed are required. Thus, theoretical interrogation is critical to provide deep understanding and possible improvement of FPP. By dividing an FPP measurement process into four steps (system calibration, phase measurement, pixel correspondence, and 3D reconstruction), we give theoretical analysis on the entire process except for the extensively studied calibration step. Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In formula (13), h j and w j can be obtained by the mathematical relationship between the two-dimensional coordinates of the light bar in the image coordinate system and the threedimensional coordinates in the world coordinate system.…”
Section: The Principle Of Volume Measurement Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In formula (13), h j and w j can be obtained by the mathematical relationship between the two-dimensional coordinates of the light bar in the image coordinate system and the threedimensional coordinates in the world coordinate system.…”
Section: The Principle Of Volume Measurement Of Materialsmentioning
confidence: 99%
“…Given the limitations of ultrasonic belt scales, some noncontact measurement methods based on the principle of optical projection have been proposed. In article [13], the authors proposed a new method for edge projector profile measurement and demonstrated the perpendicular relationship between the epipolar line and the optimal fringe angle and reconstructed the three-dimensional model of the object by using three equations. In article [14], Huang designed an optical belt scale.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the transform-based methods [17][18][19][20][21][22] (e.g., FT, window Fourier transform, and wavelet transform) just need one single fringe for phase calculation by spatial or frequency domain analysis. The FT [17,18] method is the most representative transform method, which is well-suited for high-speed 3D measurement. Nevertheless, the FT method has the inherent problem of spectrum leakage that will influence its precision in dynamic scenes.…”
Section: Introductionmentioning
confidence: 99%
“…Fringe projection profilometry (FPP) has emerged as a powerful and versatile technique in the field of optical metrology and surface profilometry. Over the years, it has gained significant attention due to its high-accuracy [ 1 , 2 ], high-speed [ 3 , 4 ], and high-resolution [ 5 , 6 ] capabilities, enabling the accurate measurement of 3D shapes and surface topography. This technology has been widely applied in industrial measurement [ 7 ], cultural relic protection [ 8 ], surgical medicine [ 9 ], artificial intelligence [ 10 ], and other fields [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%